Temporal fluctuation and reproduction of Thermocyclops decipiens (Copepoda, Cyclopoida) in an eutrophic lake of central Brazil - Padovesi Fonseca, C.=700 1 De Mendoca Galvao, L.
(Es, En)
ilus., 38 ref.
Keywords: ZOOPLANCTON; ECOSISTEMA; REPRODUCCION; COSTA RICA; FLUCTUACION TEMPORAL